Adquisición de la competencia traductológica: propuesta de una unidad didáctica de traducción general - KAMAL ZAGHLOUL, Ahmed (Didáctica. Lengua y Literatura, 2010)
This study proposes a teaching unit for direct translation from Spanish language into Arabic of nonspecialist texts. As a model of this sort of texts we have chosen two spanish cartoons. The unit that we propose is based on the Task based Approach. We are explaining some activities which are based on the usage of authentic texts, due to develop the contents of the teaching unit. This aims to improve the translatological competence of the students. We have chosen the Task-based Approach because we believe that is more adapted to the real needs of translation students than traditional teaching methods.